Subjective Perceptions and Their Characteristics of Middle School Students Regarding the Effectiveness of the “0th Period Physical Education Class” in South Korea: The Q Methodology Application - Wonjae Jeon (MDPI AG, 2021)
The aim of this study is to explore the subjective perception types and characteristics of Korean middle school students regarding participation in the “0th period physical education class”, a class involving physical movement that takes place before the start of regular school classes in the morning. This goal was achieved by applying the Q methodology, which can categorize the subjective viewpoints of research participants. The selection of the final 25 Q-samples was done by composing the Q-population. Twenty middle school students were selected as the P-sample, and Q-sorting was performed on them. The PQ method program (version 2.35) was used to perform centroid factor analysis and varimax rotation. The study presented five types with a total variance of 87%. Types 1 to 5 (N = 4, 4, 4, 5, and 3) pertained to a potent means of enhancing lesson concentration and academic performance, efficient activities to improve physical ability and a healthy body image in adolescence, the motivating power behind a stable school life and sociability development, building an upright character and successful changes in daily life, and raising awareness of the importance of participating in sports and the importance of physical activity, with eigenvalues (EVs) of 3.89, 4.48, 3.96, 5.16, and 2.58, respectively, and explanatory variances of 0.10, 0.22, 0.13, 0.33, and 0.09, respectively. Moreover, consensus statements for each factor were demonstrated as being Q24 and Q25. The findings in this study supported the academic foundation for the official introduction and activation of “0th period physical education classes” in the Korean education community for the near future.